Educación en tiempos de cuarentena: Desafíos e impactos en la educación Básica Primaria del Departamento del Choco en el municipio de Istmina - Asprilla Ortiz, Jharen Jasbleidi (Universidad Antonio Nariño, 2022)
The changes caused to the branches of the public sphere that are experienced today, product of the virus that plagues the whole world covid - 19 and that has generated a state of mandatory quarantine that prevents the normal development of daily activities; It has brought with it a series of challenges and challenges that have had to be assumed in order to take responsibility for the fulfillment of one of the fundamental rights of people, such as the right to education. This fact is precisely the vehicle that mobilizes the following article, since it seeks to identify and analyze the different challenges and impacts that the pandemic caused by covid-19 has founded in the educational field, particularly in basic and public education of the Chocó Department Municipality of Istmina. To carry it out, an exploratory and descriptive research was developed through which the information necessary for the analysis was collected, using a semi-structured interview as a collection tool that would allow to evidence the perceptions and actions regarding what is being carried out in these contexts. With this, it was possible to determine the great difficulties in terms of inequity that are experienced in the educational field in the Department of Chocó Municipality of Istmina; This new virtual education model prevents the development of daily educational activities, since it ignores the economic situations of families, thereby increasing the dropout rates in school and the low academic performance of the students.